ANALISIS FAKTOR PENYEBAB PENYAKIT JANTUNG MENGGUNAKAN METODE PRINCIPAL COMPONENT ANALYSIS (PCA) - Manullang, Sudianto; Kairani, Nerli; Sinaga, Marlina Setia; Hutapea, Brian; Nadya, Fauza; Br Barus, Jesika Casadae Wanda; Tamara, Angga; Silaban, Dewi Fortuna (LPPM Universitas Bina Bangsa, 2024)
Factor analysis is an important method in research to identify the underlying structure of complex data. Heart disease is a disease caused by a disturbance in the coronary blood vessels that causes narrowing and blockage so that it can interfere with the body's energy transportation process and also cause an imbalance between oxygen demand and oxygen supply. Various factors such as age, gender, smoking, etc. have an important role for a person to get heart disease. This study aims to analyze the factors that cause heart disease using the Principal Component Analysis (PCA) method. PCA is used to identify and reduce the dimensions of heart disease factor data. The data used in this study were obtained from journals and consisted of 7 variables. PCA successfully identified 2 main factors that explained 75% of the total variance in the data. Through dimensionality reduction, the number of variables was successfully reduced from 7 factors to 2 factors without significant information loss. This study found that the PCA method was effective in reducing the dimensionality of the data and identifying the main factors underlying the data.